THE ANALYSIS OF GENERIC STRUCTURE OF DESCRIPTIVE TEXT USED BY STUDENTS OF ELEMENTARY SCHOOL 1 PENAMBANGAN PROBOLINGGO - Indah, Chindy Hanggara Rosa (UIBU, 2022)
The difficulty found in writing is not only due to the need to generate and organize ideas using the appropriate choice of vocabulary, sentence, and paragraph organization. A descriptive text is one of the texts that can help students to improve their ideas into a text. The researcher used the qualitative method as the way to analyze the data in this research. It focused on analyzing the student’s skill of applying the generic structure of descriptive texts. The writer used the data from the students’ descriptive texts taken from the worksheet of Elementary school 1 Penambangan Probolinggo. The findings are as follows; they do not master the language features of descriptive text and lack vocabulary and got difficulties describing with effective word choice. They failed to show well-organized writing and did not use identification appropriately, the last they were still unable to transfer and develop their ideas into a written form well in composing a text and do not use the description process in writing appropriately. Finally, the researcher concluded that some students at Elementary school 1 Penambangan Probolinggo still need more practice to choose a topic that they are about to discuss and to arrange the descriptions with proper connectives.